Analysis of Problems Issuing Systematic Billing Warning Letters In The Billing System - Azizah, Nur; Proverbs Irmalis (Paspama Institute, 2023)
issuance of warning letters must be carried out by the office in order to increase the company's income (tax office). to find out company satisfaction with tax bearers, while the research method is using qualitative methods, by means of a case study approach and the collection of each data is carried out by observation and interview techniques in the form of words, writing or information around the company being observed. Meanwhile, the company's level of satisfaction with the community has not been as good as desired.